Ius Reformandi: die Entwicklung eines Staatskirchenrechts von seinen Anfängen bis zum Ende des Alten Reiches - Schneider, Bernd Christian (Jus Ecclesiasticum, 2001)
The ius reformandi defines the right of temporal authorities to regulate religion in their state. It developed not directly in the Middle Ages, as many believe, but mainly as a result of the interaction between theology, theoretical jurisprudence and legal policy and in what can be seen as three major periods: prior to the Religious Peace of Augsburg in 1555, up to the Peace of Westphalia in 1648 and then until the Holy Roman Empire ceased to exist in 1806. In this work, which is divided into three main parts corresponding to the three phases of development and considers all the significant sources, the author provides an historical survey of the development of the most important rights pertaining to the established churches in the Holy Roman Empire.